Pengaruh Keadilan Organisasi Pada Kepuasan Kerja dan Turnover Intention Karyawan BPR di Kabupaten Tabanan - Putra, A A Wisnu Yogeswara; Putra, Made Surya (E-Jurnal Manajemen, 2014)
The purpose of this study is to test the impact of organizational justice on job satisfaction and turnover intention. Respondents were 160 employees who determined using proportional random sampling method, where respondents are permanent employees other than directors and representatives who have a minimum term of 1 year. Data obtained by distributing questionnaires were analyzed using path analysis. The test results get justice organizations has a significant positive effect on job satisfaction, organizational justice has a significant negative effect on employee turnover intention and job satisfaction did not has significantly influence on employee turnover. Keywords : Organization Justice, Job Satisfaction, and Turnover Intention